Sublimation-Dissociation of Crystalline Germanium Nitride Ge3N4 and Preparation of Amorphous Oxynitride Films Ge3N4-xO1.5x - Nakhutsrishvili , Irakli; Adamya, Zurab; Stepnadze, Irakli (Progress in Chemical Science Research Vol. 9, 2023)
The question of dissociation-sublimation of \(α\)- and \(β\)-modifications of germanium nitride and their mixtures is considered. In the temperature range of 650-750oC it sublimates. In the range of \(\sim\)(750–850)oC, partial dissociation of Ge3N4 is observed, which is accompanied by evaporation of the remainder of the solid phase. About 850oC and above Ge3N4 completely dissociates. During sublimation of crystalline germanium nitride in the cold zone of the reactor, an amorphous film of oxynitride is obtained.